Pejorative Words Indicating Indonesian Hate Speech - Citra Suryanovika; Laily Nur Affini (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2023)
The study aims to identify the pejorative words in @detiknews’ comments and hate speech targets. This study was qualitative research, specifically descriptive content analysis. The researchers took the data from Indonesian comments in eighteen news of @detiknews’ Instagram account. The researchers used MAXQDA to show the results of the coding process. The study has found seven categories of Thurlow: social personality, uncategorized, top-5, racist, homophobic, phallocentric, and physicality. In this study, pejorative words were in the standard and non-standard Indonesian, local languages (Javanese, Betawi), vulgar slang, and animal metaphors. The study has classified pejorative words (Thurlow, 2001) as directed or generalized hate speech (Elsherief et al., 2018). The findings show that directed speech was a personal matter. To sum up, pejorative words indicating hate speech in Indonesia are not randomly used; it intends to show the users’ disagreement toward the publisher or another user’s comment: it is addressed explicitly to either directed or generalized targets.